(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
The Natural Monopoly Challenge To keep pace with rapid change, regions require dynamic learning systems that develop both individual competencies and adaptive capabilities. Regional competitive advantage has shifted from natural resource proximity to the ability to operationalize human capital for social and economic prosperity. Despite pressure from scholars, policymakers, and employers to adapt to rapid socio-economic and technological shifts, public postsecondary systems remain structurally resistant to transformation. This report argued that these systems exhibit the defining traits of a natural monopoly. Originating in the late 19th century, natural monopolies emerged in essential sectors, such as telecommunications, energy, water, and transportation, that required heavy capital investment. Consequently, policymakers granted these providers monopoly protections in exchange for guaranteed service investment and operation. With 89 percent of the world’s 235 million students enrolled in public institutions, this market dominance creates structural barriers to innovation. Natural Monopoly in Higher Education In many regions, four entrenched factors act as natural monopoly barriers to innovation: 1) credentialism culture; 2) structural advantages; 3) regulatory protections; and 4) the monopoly culture of incumbent institutions. The following analysis examined the emergence of open learning providers and the system tensions surrounding barriers to open learning. To address these barriers, the Open Learning Charter established a framework that prioritizes competency over institutional affiliation and recognizes all forms of learning, formal, informal, and experiential. By decoupling assessment from learning pathways and directing funding directly to learners, the Charter shifts the ecosystem toward interoperability and public stewardship of digital infrastructure. The Clinic This 60-minute interactive workshop used a future-state scenario set in 2029, where "Country X" has mandated the Open Learning Charter. Participants, representing stakeholders such as learners, employers, and policymakers, must design a framework to operationalize the Charter’s commitments. Utilizing the four-level Iceberg method, groups identified and prioritized the events and patterns, structures, and mental models that challenge or support the transition to a competency-based, decoupled learning ecosystem. The session specifically challenged participants to analyze how the Charter impacts their stakeholder group and to determine how decoupling learning can be introduced to maximize societal impact. The session concluded with a presentation of stakeholder-specific impacts and essential design features to maximize societal benefit. Keywords: Natural monopoly, open learning, competency-based practices, Open Learning Charter